The Influence of the Teams Games Tournament Learning Model on the Learning Outcomes of Students at Quhas Primary School - Nur Analisa Ramadani; Shalahudin Shalahudin; Ahmad Sayuti Nainggolan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the extent to which the implementation of the Team Game Tournament (TGT) learning Model, supported by Wordwall, infIuences students’ cognitive learning outcomes in the IPAS subject. This study employs a quantitative approach using a quasiexperimental method with a non-equivalent control group design. The population in this study consists of all fourth-grade students at MI QUHAS Primary School, with a sample size of 40 students divid into an experimental class and a control class. Data collection was conducted through tests, including a pre-test and a pos-test. The results of the study indicate that the averagge postest score in the experimental class was 75.25, high than that of the control class, which achieved an average of 62.00. This average difference of 13.25 points indicates a greater improvement in learning outcomes in the class that used the TGT Model assisted by Wordwall. Furthermore, based on the results of the Independent Sample t-Test, a significans value of 0.030 (< 0.05) was obtain, indicating a significans diference between the two classes. Thos, it can be concluded that the implementation of the TGT learning Model supported by the Wordwall platform significantly improves the cognitive learning outcomes in science for fourth-grade students.